2011
DOI: 10.1007/s11249-011-9773-y
|View full text |Cite
|
Sign up to set email alerts
|

Role of Nano-YbF3-Treated Carbon Fabric on Improving Abrasive Wear Performance of Polyetherimide Composites

Abstract: A method for surface treatment of carbon fabric with nano-particles of rare earth salt (ytterbium fluoride-YbF 3 ) was tried first time in the authors' laboratory to enhance the fiber-matrix interface, and has been reported here. In this article authors have reported on the performance evaluation of composites developed from the four fabrics treated with various doses viz. 0, 0.1, 0.3, and 0.5 wt% of YbF 3 . The abrasive wear performance of these composites was evaluated by abrading the composites against sili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…Maximum ILSS and FS were shown by C 90 composite, which indicates that 90 min treatment was an optimum dose for this type of treatment and most effective in improving adhesion between fiber and matrix. This enhanced adhesion [12][13][14][15] led to an improvement in all mechanical properties of the composites such as strength (tensile, flexural and ILSS) and modulus (tensile and flexural). The enhancement was maximum in ILSS and minimum for TS and toughness.…”
Section: Effect Of Treatment On the Properties Of Compositesmentioning
confidence: 99%
See 1 more Smart Citation
“…Maximum ILSS and FS were shown by C 90 composite, which indicates that 90 min treatment was an optimum dose for this type of treatment and most effective in improving adhesion between fiber and matrix. This enhanced adhesion [12][13][14][15] led to an improvement in all mechanical properties of the composites such as strength (tensile, flexural and ILSS) and modulus (tensile and flexural). The enhancement was maximum in ILSS and minimum for TS and toughness.…”
Section: Effect Of Treatment On the Properties Of Compositesmentioning
confidence: 99%
“…FTIR-ATR spectroscopic analysis of CF showed that treatments significantly influenced the chemical structure of its surface and led to an inclusion of oxidative polar functional groups. [12][13][14][15] Figure 4 shows FTIR-ATR of untreated and treated (only with optimized doses) CF. Significant variations in % absorbance was observed in the range of 1000-2000 cm À1 wave-number, which indicates presence of functional groups on a fiber's surface.…”
Section: Effect Of Treatment On the Properties Of Cfmentioning
confidence: 99%
“…At present, the common surface modification methods of CF include wet chemical modification (polymer sizing agent, chemical grafting, and electrochemical modification with acid), [9][10][11][12][13] dry modification (ion treatment, high energy irradiation, and heat treatment), [14][15][16] and multi-scale modification (electrodeposition, chemical vapor deposition). [17][18][19][20] Sizing agent is used to coat CF surface, which can solve the problems of brittle fracture and fluffy tow of CF in the production process. [21,22] Additionally, sizing agent can provide enough surface finish for CF, improve surface wettability, increase surface reactive groups, and enhance the interface binding ability between CF and matrix resin.…”
Section: Introductionmentioning
confidence: 99%
“…The performance of CFRPs depends not only on the material components but also on the interfacial interaction between the CF and the polymer. Accordingly, various methods have been employed to treat CF, 16 such as sizing, [17][18][19][20] acid oxidation, [21][22][23] plasma treatment, 24,25 and rare earth treatment 26 . Among them, the sizing treatment is the most commonly used method which not only protects CF from fragmenting and fuzzing during processing but also enhances the interfacial interaction between the CF and the polymer matrix via various functional groups.…”
Section: Introductionmentioning
confidence: 99%